Rhipha ignea sp. nov. (Arctiini: Erebidae: Lepidoptera), new species of the flammans group, from Peruvian Amazonia - Grados, Juan (2016)
Rhipha ignea, a new species from department Loreto, Peruvian Amazonia, is described and illustrated.